2020
DOI: 10.18383/j.tom.2020.00005
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Interstitial Fluid Pressure and Velocity in Head and Neck Cancer Based on Dynamic Contrast-Enhanced Magnetic Resonance Imaging: Feasibility Analysis

Abstract: We developed and tested the feasibility of computational fluid modeling (CFM) based on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for quantitative estimation of interstitial fluid pressure (IFP) and velocity (IFV) in patients with head and neck (HN) cancer with locoregional lymph node metastases. Twenty-two patients with HN cancer, with 38 lymph nodes, underwent pretreatment standard MRI, including DCE-MRI, on a 3-Tesla scanner. CFM simulation was performed with the finite element method in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…The pre-contrast T 1w FAs data were fitted for T 10 mapping as detailed elsewhere [ 39 ]. The R 1 data with time were fitted to Equation [ 6 ] using the AIF was extracted from the carotid artery [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pre-contrast T 1w FAs data were fitted for T 10 mapping as detailed elsewhere [ 39 ]. The R 1 data with time were fitted to Equation [ 6 ] using the AIF was extracted from the carotid artery [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…CA enters passively into the EES via diffusion from the blood plasma in a hyperpermeable capillary, which is described by K trans . To account for the bulk flow of spatially varying CA into the EES within the tumor [43][44][45]49], the normalized K trans value is incorporated into the continuity equation (Equation ( 8)), including the Starling equation of net flux change between vascular and lymphatic vessels. Note, a voxel-wise K trans value was normalized and included in the equation as a factor to convey relative vascular leakiness.…”
Section: Computational Fluid Modeling Theory and Analysismentioning
confidence: 99%
“…To assess the robustness of the approach, IFP computed from the DCE-MRI approach was compared with the standard WIN method [39,41]. The results of previous studies suggested that the microvascular and interstitial hydraulic conductivities influence the outcome of the porous media fluid flow simulation [41][42][43][44][45][46]. However, the correlations need further validation to be part of clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the spatial scales of in vivo assessments of tumor physiology are typically limited to 0.25-5 mm (Frangioni, 2008;Ramamonjisoa and Ackerstaff, 2017), these techniques do enable measurement of temporal dynamics within the tumor microenvironment (Yankeelov et al, 2016b), such as vascular perfusion (Yankeelov et al, 2014;Yankeelov and Gore, 2009), metabolic activity (Castell and Cook, 2008), or interstitial flow (Kingsmore et al, 2018;LoCastro et al, 2020). These data types can also be acquired in 3D to evaluate an entire tumor volume, permitting investigation of regional differences within a tumor (e.g., regions of necrosis or proliferation, gradients of oxygen or nutrients) (Kim and Gatenby, 2017;Syed et al, 2020).…”
Section: Mathematical Modeling Of Cancer At the Tissue And Organ Scales Cancer Physiology At The Tissue And Organ Scalementioning
confidence: 99%